Laju paparan dan dosis radiasi dari pasien terapi kelainan kelenjar tiroid dengan pemberian radiofarmaka Iodium-131 - Ahmad Mutohar; Wahyu Setiabudi; Rini Shintawati (Youngster Physics Journal, 2017)
Research about exposure and dose rate from patients with thyroid gland disorders therapy who received radiopharmaceutical Iodine-131 is done by direct measurement using a survey meter. In this study, the exposure rate collected from 37 patients who received doses of radiopharmaceutical therapy with activity ≤ 30 mCi and 13 patients who received doses of radiopharmaceutical therapy with activity> 30 mCi. Exposure rate of each patient was subsequently changed in the form of the dose rate. The results obtained that all patients who received a dose of a radiopharmaceutical with activity ≤ 30 mCi, produce dose rate below the maximum extent permitted to leave the hospital.  While patients who received doses with activity > 30 mCi, produce a dose rate above generate maximum extent permitted to leave the hospital. Besides that, the research also analyzed the reduction of dose rate from each patient. A decrease of dose rate (within 1 hour after administration of radiopharmaceutical) is affected by the excretion rate and rate of uptake of iodine in the blood.  Specially, patient who received a dose with activity > 30 mCi, efective half-life value is determined from a decrease of the dose rate each patient. The results obtained that effective half-life of I-131 in the body of every patient in the range of 6 to 14 hours. Patient H had the shortest effective half-life and patient M has longest effective half-life. The difference of effective half-life of I-131 affected by  biological elimination/ biological half-life of each patients.Keywords: Exposure rate, dose rate, Iodine-13 therapy patients, effective half-life